Application of Kalman Filter to Estimate Dynamic Hedge Ratio in Pairs Trading Strategy: A Case Study of the Automobile Industry - Mohammad Javad Nourahmadi; Marziyeh Norahmadi (تحقیقات مالی)
Objective: Pairs trading strategies have been around since the mid-1980s and have gained widespread acceptance in recent years. A pairs trading strategy is one of the forms of statistical arbitrage done to make a profit. It bases on the return related to the average spread between pairs of financial securities. The purpose of this research is to investigate the application of the Kalman filter to estimate the dynamic hedge ratio in the pairs trading strategy. The main question of this article is whether individual investors can make a profit by using this trading strategy or not.Methods: The second step was related to the pairs trading strategy, introducing the trading rules and determining the thresholds for buying, selling, and exiting the transaction. Any significant deviation from the average in the spread between two securities was a signal to trade and make a profit. We sold or bought the spread when the spread deviated as much as the positive or negative side of the two standard deviations from the average, and when the spread converges within the positive or the negative halfway point of the standard deviation, we exited the trade to make a profit. Of course, as with all trading strategies, the more you use them, the less likely you will make a profit. In this research, the co-integration method was used to select the pair of stocks, and based on the space-state approach and using the Kalman filter algorithm, the dynamic hedge ratio was estimated to provide trading signals. Trading signals were used to develop a pairs trading strategy between 26 companies in the automobile industry on the Tehran Stock Exchange during the period 2016 to 2020.Results: According to the co-integration results, out of the 26 stocks we selected for analysis, only 16 stocks had a co-integration relationship. According to the Kalman filter method, the CAGR was 0.11 and the Sharp Ratio was 3.06.Conclusion: The results obtained from the Sharp ratio and Compound annual growth rate (CAGR) showed that the pairs trading strategy in the period under review was profitable in the automobile industry. The results also proved the superiority of the Kalman filter method over the co-integration method for pairs trading.